Endovascular treatment of bilateral intracranial vertebral artery aneurysms: an algorithm based on a 10-year neurointerventional experience. Issue 3 (13th August 2020) - Zhang, Yisen; Tian, Zhongbin; Zhu, Wei; Liu, Jian; Wang, Yang; Wang, Kun; Zhang, Ying; Yang, Xinjian; Li, Wenqiang
Abstract : Background: The management of bilateral intracranial vertebral artery dissecting aneurysms (IVADAs) is controversial, and requires the development of endovascular treatment modalities and principles. We aim to investigate the endovascular treatment strategy and outcomes of bilateral IVADAs. Methods: We identified all bilateral IVADAs at a high-volume neurointerventional centre over a 10-year period (from January 2009 to December 2018). Radiographic and clinical data were recorded, and a treatment algorithm was derived. Results: Twenty-seven patients with bilateral IVADAs (54 IVADAs in total, 51 unruptured, 3 ruptured) were diagnosed. Four patients (14.8%) received single-stage endovascular treatment, 12 patients (44.4%) with staged endovascular treatment and 11 patients (40.8%) with unilateral endovascular treatment of bilateral IVADAs. Thirty-six IVADAs (85.7%) have complete obliteration at the follow-up angiography. Two of three ruptured IVADAs with stent-assisted coiling recanalised, and had further recoiling. Three patients (11.1%) have intraprocedural or postprocedural complications (two in single-stage and one in staged). Twenty-five patients (92.6%) had a favourable clinical outcome, and two patients (7.4%, all in single-stage) showed an unfavourable clinical outcome at follow-up. For the patients with unilateral reconstructive endovascular treatment, the contralateral untreated IVADAs were stable and had no growth or ruptured during follow-up period. None of all IVADAs had rebleeding during the clinical follow-up. Conclusions: Endovascular treatment can be performed in bilateral IVADAs with high technical success, high complete obliteration rates and acceptable morbidity/mortality. Contralateral IVADAs had low rates of aneurysm growth and haemorrhage when treated in a staged/delayed fashion.